Homeostatic proliferation and IL-7R alpha expression do not correlate with enhanced T cell proliferation and protection in chronic mouse malaria. - Robin Stephens; Benedict Seddon; Jean Langhorne (PLoS ONE)
While chronic infection has been shown to enhance protection from disease caused by several pathogens, the mechanisms are not known. The gamma-c family of cytokines IL-7, IL-2, and IL-15 are implicated in homeostatic proliferation, which is thought to maintain T cell memory. However in chronic infection, prolonged antigen exposure itself may contribute to lymphocyte survival. We have previously observed that chronic malaria infection enhances protection to re-infection, as well as enhancing B cell responses. Here, we show that chronic Plasmodium chabaudi malaria infection in mice enhances the expansion of CD4(+) T cells in a second infection, and that this correlates with increased expression of the IL-2/15 Receptor beta (CD122) on memory T cells, as well as increasing IL-2 producers on re-infection. IL-2 has been recently linked to improved secondary proliferation, while the role of IL-7 in maintenance of CD4(+) memory cells has been demonstrated in homeostatic proliferation, but its role in protective memory populations in infectious disease protective has not been fully investigated. Increased IL-7Rα (CD127) expression correlated, as previously reported with increased turnover of CD4 memory cells, however, this was not linked to protection or enhanced response to rechallenge, These data support the idea that antigen or IL-2 production resulting from chronic stimulation may play a role in an enhanced secondary T cell response.